Topic familiarity and story continuation in young English as a foreign language learners’ writing tasks - Bui, Gavin; Luo, Xueya (Studies in Second Language Learning and Teaching, 2021)
Prior research demonstrates that primary and secondary school teachers often find teaching young learners to write in a second language a slow and effortful process. Moreover, students in this age range lack the motivation to write. Therefore, it is important to explore the EFL writing pedagogy suitable for young learners. The present study investigated how story continuation (with or without reading input) under different topic familiarity conditions serves as a viable pedagogical means for secondary school students. Ninety-one Chinese students in four intact classes of comparable proficiency levels were assigned four writing task conditions in a 2 ⨉ 2 factorial design. Group 1 (Fam) was provided with the beginning of a familiar story in L1 Chinese and was required to complete the story in L2 English. Group 2 (UnFam) had the same task as Group 1, with an unfamiliar story. Group 3 (Fam+Input) was initially provided with the complete familiar story in Chinese (the same story as Group 1) as reading input and were then instructed to write the story in English with the reading material taken away. Group 4 (Unfam+Input) received the full unfamiliar story in Chinese (the same story as Group 2) as input before writing. Again they were not allowed to refer to the reading in the composing process. The results revealed that the young learners who wrote on familiar topics (Groups 1 and 3) produced longer texts and demonstrated greater lexical diversity than those with unfamiliar stories (Groups 2 and 4), although topic familiarity did not affect their writing quality or lexical sophistication. As for the story continuation conditions, students who completed writing the story without the L1 reading input on the topics (Groups 1 and 2) developed longer compositions and better writing quality than those with such input (Groups 3 and 4), although their lexical profiles (both lexical diversity and lexical sophistication) remained uninfluenced. Pedagogical implications for EFL writing among young learners were also discussed in the present study.